Evolution characteristics of crack and energy of low-grade highway under impact load. Issue 9 (29th July 2022) - Lin, Qindong; Feng, Chun; Zhu, Xinguang; Zhang, Genghao; Li, Shihai
ABSTRACT: To analyse the feasibility of the low-grade highway as a launch site in military applications and improve the pavement crushing technology in civilian applications, this study investigates the evolution characteristics of a low-grade highway under impact load, including deflection, crack, and energy, via the continuum–discontinuum element method (CDEM). To this end, this paper proposes an energy statistics algorithm, and the correctness is verified. Then, a quarter three-dimensional numerical model of an asphalt concrete highway is established, and the effectiveness of CDEM in simulating the deflection of the highway under impact load is validated. Finally, an existing asphalt concrete highway structure is selected to study the evolution characteristics via numerical simulation. The results demonstrate the consistency between the variations of deflection at the load centre and the impact load. The deflection is primarily caused by the compressive deformation of subgrade. Crack planes mainly occur when the impact load increases rapidly. The variation of various constituent energies is different but closely related to the change in impact load.